Towards a supervised machine learning algorithm for cyberattacks detection and prevention in a smart grid cybersecurity system - Banda, Takudzwa Vincent (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.